2010
DOI: 10.1007/s10529-010-0490-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of two types of bioactive scaffold used for tendon–bone interface healing in the reconstruction of anterior cruciate ligament

Abstract: Fibrin glue combined with bone morphogenetic protein (BMP) and recombined bone xenograft (RBX), were compared to evaluate their effect on the tendon-bone interface healing. The interface of fibrin glue-BMP developed new cartilage but the new bone was thinner whereas the interface of RBX had large areas of chondrocyte-like cells, bone formation and an immature neo-enthesis structure. At 12 weeks, bone mineral density of RBX group (152 ± 52 cm(3)) and fibrin glue-BMP group (109 ± 13 cm(3)) was calculated by micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…Nowadays, hamstring tendon autografts are the most preferred ones in clinical practice (Chechik et al 2013), with significantly less donor site morbidities than bone-patellar tendon-bone autografts (Poolman et al 2007). However, the tendon-bone healing of soft tissue tendon grafts is weak in ACL reconstruction, especially in the early stage, and a number of methods have been tried to enhance the tendon-bone healing (Hashimoto et al 2011;Zhang et al 2011;Dong et al 2012;Kuang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, hamstring tendon autografts are the most preferred ones in clinical practice (Chechik et al 2013), with significantly less donor site morbidities than bone-patellar tendon-bone autografts (Poolman et al 2007). However, the tendon-bone healing of soft tissue tendon grafts is weak in ACL reconstruction, especially in the early stage, and a number of methods have been tried to enhance the tendon-bone healing (Hashimoto et al 2011;Zhang et al 2011;Dong et al 2012;Kuang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 27 included in vivo studies, two were human trials (Petruskevicius et al, 2002;Mochizuki and Ochi, 2015) and 25 were animal studies. More than half of the animal studies (n = 14) utilized a rabbit model (Zhang et al, 2011;Li et al, 2012Li et al, , 2017Jiang et al, 2014;Han et al, 2015;Chou et al, 2016;Chung et al, 2017;Lee et al, 2017;Cai et al, 2018;Hu et al, 2018;Chen P. et al, 2019;Han F. et al, 2019;Learn et al, 2019), eight studies used rats (Loeffler et al, 2013;Zhao et al, 2014Zhao et al, , 2015aKovacevic et al, 2015;Zhang et al, 2018;Zhu Q. et al, 2019), and three studies used pigs (Fleming et al, 2009;Vavken et al, 2012;Li et al, 2014). The involved patients and animals were mature, and no minor or immature animal model had been investigated in previous studies so far as searched.…”
Section: Data Extractionmentioning
confidence: 99%
“…therefore, recombined bone xenograft (RBX), a new type of biosynthetic material which can be directly incorporated into injectable CPC, has been suggested to be more effective in augmenting bone ingrowth in animal models (20). RBX has already been used as a BMP carrier, showing accelerated tendon-bone healing (21). Moreover, Weimin et al (22) showed that RBX further accelerated tendon-to-bone healing and provided higher maximum loads to failure when compared with injectable CPC alone after ACL reconstruction in a rabbit model.…”
Section: Bone Proteins and Growth Factorsmentioning
confidence: 99%